Peran Otoritas Jasa Keuangan (OJK) Dalam Pengawasan Bank Digital Untuk Mencegah Praktik Investasi Ilegal - Nugraha, Naufal Satria; Alfarizky, Hertasandho Maynaka; B, Baidhowi (Media Hukum Indonesia (MHI), 2025)
The rapid development of digital technology has driven the transformation of the financial services sector, including the emergence of digital banks. Digital banks offer convenience and efficiency but also open up opportunities for illegal investment practices that often misuse the name or platform of digital banking services. This study aims to analyze the role and effectiveness of the Financial Services Authority (OJK) in preventing illegal investment practices through digital banks. This research uses a library research method by examining literature, regulations, official reports, and case studies of illegal investments in Indonesia. The results show that OJK has implemented various supervisory measures, both through regulation and by establishing the Investment Alert Task Force (SWI). However, the effectiveness of supervision still faces challenges such as limited human resources, increasingly complex digital crime methods, and the need for more adaptive regulations. Therefore, strengthening inter-institutional synergy, improving public digital literacy, and reforming supervisory policies are crucial to ensure that the development of digital banks aligns with consumer protection and the prevention of illegal investment practices.